In situ evaluation of Ni/CeO2 catalysts synthesized via polymeric precursor method by XAS for CO2 reduction - Assis, Matheus S. [UNESP]; Lucas, Marcela A. [UNESP]; Briois, Valérie; Possato, Luiz G. [UNESP] (Elsevier, 2025)
Ni/CeO2 catalysts were synthesized via the polymeric precursor method to investigate the effect of varying Ni load (5, 10, and 20 wt%) on the CeO2 structure, focusing on their structural and catalytic properties in converting CO2 to CH4. Although well studied, the polymeric precursor method is rarely explored for Ni/CeO2 in CO2 conversion. We demonstrate a systematic study of synthesis and characterization that the Ni incorporates in CeO2 structure and promotes the Ni-O-Ce solid solution formation, which is important in the selective conversion of CO2 into CH4. The CO2 conversion per Ni0 atom was 70 % higher (expressed as TON in s−1) when 20 % of the Ni-Ce-O species were present, as observed in the 5 and 10 wt% Ni load samples comparison. Long-term catalytic testing with the 10 wt% Ni load sample revealed the catalyst is highly active and 100 % selective to CH4. For all catalysts, the carbon balance was 100 %.
Keywords: CO2 reduction; In situ characterization; Nickel catalysts; Polymeric precursor method; Time-resolved experiment; X-ray absorption spectroscopy